Improvement of the Efficiency of Adolescents’ Interpersonal Interaction in Conflict Resolution - Vasilievna Shimanovskay, Yanina a (2021)
The relevance of the examined problem results from the fact that the adolescents’ behaviour and their inability to overcome conflict situations are of an acute social nature. In this regard, the article is aimed at identifying the causes of early motherhood and finding ways to solve the problem in the context of social and pedagogical work. The leading research methods of this problem are psychological techniques that allow one to identify the causes of interpersonal conflicts among adolescents and to develop credible practical recommendations aimed at improving the efficiency of adolescents’ interpersonal interaction. Based on the obtained data, the authors have developed specific diagnostic, correctional and training programs for behaviour correction in particular conflict situations.